Evidence ex officio in arbitration - Taboada Mier, José Carlos (2018)
This article seeks to demonstrate the thesis that ex officio evidence in arbitration is unnecessary and should be eliminated from it or its application reduced to the minimum possible. For this, the author provides an approximation of the concept of ex officio proof and describes, through the relevant regulations, its use in arbitration. Finally, it analyzes the admissibility of the same, stating that it must opt for a limited admissibility for certain cases, and that it respects the procedural guarantees of the parties.